Erratum to: New cosmic ray observations at Syowa Station in the Antarctic for space weather study - Kato Chihiro; Kihara Wataru; Ko Yukino; Kadokura Akira; Kataoka Ryuho; Evenson Paul; Uchida Satoru; Kaimi So; Nakamura Yoshiaki; Uchida Herbert Akihito; Murase Kiyoka; Munakata Kazuoki (Journal of Space Weather and Space Climate, 2021)
Due to confusion in the proof correction process, the author’s proof corrections were not correctly taken into account. The corrections are listed below, highlighted by a boldface font.